The Experience of Survival : Determinants of Export Survival in Lao PDR - Stirbat, Liviu; Record, Richard; Nghardsaysone, Konesawang (Elsevier, 2015)
This paper explores monthly, firm-level customs records from Laos in the period 2005–10. We analyze the role of two important and related determinants of export survival, experience, and networks, which are particularly relevant for developing countries. We go beyond previous studies by disaggregating contract terminations to consider the possibility of upgrades to superior products. Having prior experience with the export product and destination and strong networks of similar firms has a strong positive impact on chances of simple export survival. The likelihood of upgrading is boosted by destination experience but lowered by familiarity with the product.